Discrimination of poisonous and medicinal plants with similar appearance (Asarum heterotropoides vs. Cynanchum paniculatum) via a fusion method of E-nose, E-tongue, LC-HR-Q-TOF-MS/MS, and electrochemical fingerprint spectra - Zhang, Xin-Ru; Chen, Yue-Hua; Zhang, Jia-Nuo; Wang, Wen-Yu; Sun, Rui-Bo; Ding, Zi-Xuan; Zhang, Hui; Xie, Ming; Kang, Ting-Guo; Song, Hui-Peng (Frontiers in Chemistry, 2025)
IntroductionThe similarity in appearance of poisonous and medicinal plants, such as Asarum heterotropoides (AH) and Cynanchum paniculatum (CP), poses safety risks due to frequent confusion. Since AH contains toxic ingredients, the traditional methods of olfactory and gustatory identification cannot be used to distinguish AH from CP.MethodsTo differentiate them systematically, we proposed a novel strategy based on dual electronic sensors (DES) and dual fingerprint spectra (DFS). The DES included two intelligent sensors, namely the E-nose and E-tongue, which differentiated AH and CP based on odor and taste, respectively. DFS comprised chemical fingerprint spectra obtained through LC-HR-Q-TOF-MS/MS and electrochemical fingerprint spectra derived from the Belousov-Zhabotinsky reaction, differentiating AH and CP by their specific and overall compositions, respectively. To our knowledge, this was the first time that the E-nose, E-tongue, LC-HR-Q-TOF-MS/MS, and the Belousov-Zhabotinsky reaction were combined to identify AH and CP.Results and discussion With the E-nose, we identified 25 major odor components in AH and 12 odor components in CP in a single run of 140 s. Using the E-tongue, bitterness and astringency were identified as their primary taste differences. Furthermore, 91 compounds in AH and 90 compounds in CP were identified through LC-HR-Q-TOF-MS/MS. Both AH and CP shared nitrogenous compounds, volatile oils, organic acids, and lignans. However, AH uniquely contained coumarins and flavonoids, while CP contained steroidal compounds and saccharides. Notably, AH also possessed distinct toxic components, specifically aristolactam I, aristolochic acid D, and safrole. Based on the Belousov-Zhabotinsky reaction, we obtained the electrochemical fingerprint spectra of AH and CP, thereby facilitating further distinction between these two herbs. Through the combination of electrochemical fingerprint spectra with principal component analysis (PCA) or orthogonal partial least squares-discriminant analysis (OPLS-DA), the accuracy of this method reached 100%. Through the fusion strategy, the odors, tastes, components, and electrochemical properties of AH and CP have been systematically analyzed.